Liquefaction triggering and post-liquefaction deformation of laminated deposits. Issue 124 (September 2019) - Tasiopoulou, Panagiota; Giannakou, Amalia; Chacko, Jacob; de Wit, Sjoerd
Abstract: As part of dynamic stability evaluations of earth embankments founded on laminated sand and clay deposits, the need to characterize their cyclic resistance became critical for the assessment of the embankment behavior and subsequent decisions on liquefaction mitigation measures. Due to lack of experimental and case history data on the effective stress behavior of such deposits, which are typically encountered in tidal and alluvial depositional environments, advanced laboratory tests on high quality undisturbed samples and numerical simulations using advanced constitutive models were performed to gain insight on liquefaction triggering and post-liquefaction accumulation of deformations under level and sloping ground conditions of such formations. Results indicated that the presence of clay laminations within sand deposits tends to increase the liquefaction triggering resistance. The increase in liquefaction resistance becomes more pronounced as the percentage of clay laminations increases. Numerical analyses results also indicated that void redistribution effects, often related to strain localization effects, tend to reduce as the thickness of sand laminations decreases, or as the clay lamination percentage increases. Highlights: Experimental and numerical investigation of laminated deposits showed that /clay laminations increase the liquefaction resistance. The presence of the clay laminations tends to limit the development of strain localization. Void redistribution effects diminish as the thickness of sand laminations decreases, or as the percentage of clay laminations increases.